Intermediate and definitive hosts of Schistosoma mansoni in Corrientes province, Argentina - Borda, Carlos Edgardo (2006)
Fil: Borda, Carlos Edgardo. Universidad Nacional del Nordeste. Facultad de Medicina; Argentina.